Does intranasal steroid spray technique affect side effects and compliance? Results of a patient survey. Issue 11 (20th October 2017) - Ganesh, V; Banigo, A; McMurran, A E L; Shakeel, M; Ram, B
Abstract: Background: Intranasal steroid sprays are fundamental in the medical management of inflammatory rhinological conditions. Side effects are common, but these may be related to the method of application rather than the medication itself. Methods: A survey was distributed to patients using intranasal steroid sprays at the ENT out-patient clinic at Aberdeen Royal Infirmary over three months. This evaluated the spray technique used, side effects and compliance. Results: Of 103 patients, 22 patients (21.4 per cent) reported side effects, including nasal irritation and epistaxis. Of the 20 patients with epistaxis, 80 per cent used an ipsilateral hand technique ( p = 0.01). Thirty patients demonstrated poor compliance because of lack of symptom improvement or side effects. Seventy-seven per cent of this group used the ipsilateral hand technique. Conclusion: Patients who used their ipsilateral hand to apply the intranasal steroid spray were more likely to develop epistaxis and have poor compliance than those who used other techniques. Patients who struggle with compliance because of side effects should avoid this method of intranasal steroid application.